Enzymatic modifications of pea protein and its application in protein-cassava and corn starch gels - Ribotta, Pablo Daniel (2012)
The interactions between starch and proteins during processing influence pasting and rheological properties of starch and produce modifications on starch gel structure. Enzymatic modifications have been proposed for overcoming the limitations of using proteins as food ingredients. This work aimed to study the impact of native and enzymatically modified pea proteins on the properties of protein-starch (from cassava or corn) gels. Pea protein isolate (PPI) was incubated with endopeptidase (AL) or microbial transglutaminase (TG). Pasting profile, rheological behaviour and water retention capacity of protein-starch gels were analyzed. Protein (native and enzymatically modified) incorporation increased the viscosity of both corn and cassava starches during gel preparation. However, the hydrolyzed protein reduced drastically the increment of viscosity of protein-starch gels. The addition of PPI led to corn starch network that shifted from an elastic-like nature to a more viscous-like, whereas the opposite effect was observed in cassava gel network. TG- and AL-treated proteins led to a decrease of both G' and G' moduli of protein-starch gels, and AL-treated proteins showed the highest decrease on these parameters. Hydrolyzed proteins also favoured the syneresis of the protein-corn starch gel, whereas crosslinked proteins tended to reduce it. Enzymatic modifications of pea proteins affected significantly pasting and rheological properties of protein-starch gels. © 2011 Elsevier Ltd.